2019
DOI: 10.1016/j.celrep.2019.10.045
|View full text |Cite
|
Sign up to set email alerts
|

Non-Genetic Intra-Tumor Heterogeneity Is a Major Predictor of Phenotypic Heterogeneity and Ongoing Evolutionary Dynamics in Lung Tumors

Abstract: Highlights d Lung squamous cell carcinoma has a moderate level of intratumor genetic heterogeneity d Transcriptomic heterogeneity impacts cancer pathways, driving phenotypic heterogeneity d Neo-epitope burden negatively correlates with immune infiltration d Non-genetic heterogeneity influences tumor evolutionary dynamics

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
77
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 108 publications
(81 citation statements)
references
References 56 publications
4
77
0
Order By: Relevance
“…Generation of thousands of artificial pseudo-bulk mixtures. Using the testing datasets from the quality control step, we generated matrices containing 1000 pseudobulk mixtures (matrix T in equation (1) from "Computational deconvolution: formulation and methodologies") by adding up count values from the randomly selected individual cells. The minimum number of cells used to create the pseudo-bulk mixtures (pool size) for each of the five datasets was 100 and the maximum possible number was determined by the second most abundant cell type (rounded down to the closest hundred, to avoid non-integer numbers of cells), resulting in n = 100, 700, and 1200 for Baron; n = 100, 300, and 400 for PBMCs; n = 100 and 200 for GSE81547; n = 100 and 200 for the kidney dataset and n = 100 for E-MTAB-5061.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Generation of thousands of artificial pseudo-bulk mixtures. Using the testing datasets from the quality control step, we generated matrices containing 1000 pseudobulk mixtures (matrix T in equation (1) from "Computational deconvolution: formulation and methodologies") by adding up count values from the randomly selected individual cells. The minimum number of cells used to create the pseudo-bulk mixtures (pool size) for each of the five datasets was 100 and the maximum possible number was determined by the second most abundant cell type (rounded down to the closest hundred, to avoid non-integer numbers of cells), resulting in n = 100, 700, and 1200 for Baron; n = 100, 300, and 400 for PBMCs; n = 100 and 200 for GSE81547; n = 100 and 200 for the kidney dataset and n = 100 for E-MTAB-5061.…”
Section: Methodsmentioning
confidence: 99%
“…Moreover, understanding differences in cell type composition in diseases, such as cancer will enable researchers to identify discrete cell populations, such as specific cell types that could be targeted therapeutically. For instance, active research on the role of infiltrating lymphocytes and other immune cells in the tumor microenvironment is currently ongoing 1 – 3 (e.g., in the context of immunotherapy) and it has already shown that accounting for the tumor heterogeneity resulted in more sensitive survival analyses and more accurate tumor subtype predictions 4 . For these reasons, many methodologies to infer proportions of individual cell types from bulk transcriptomics data have been developed during the last two decades 5 , along with new methods that use single-cell RNA-sequencing (scRNA-seq) data to infer cell proportions in bulk RNA-sequenced samples.…”
Section: Introductionmentioning
confidence: 99%
“…Most tumours are comprised of a phenotypically diverse population of cancer cells, driven by a complex array of genetic and phenotypic alterations that disrupt normal cell cycle and cellular processes at multiple levels, including genomic, transcriptomic and influences from the tumour microenvironment ( Prasetyanti and Medema, 2017 ; Shibue and Weinberg, 2017 ; Sharma et al, 2019 ; Tripathi et al, 2020 ). This diversity is known as intra-tumour heterogeneity and is thought to play a crucial role in the development of treatment resistance ( Prasetyanti and Medema, 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…Inter-patient heterogeneity in NSCLC is due in part to the presence of cell subtypes: squamous, adenocarcinoma, and large-cell. Intra-patient heterogeneity is manifested by multiple primaries and dissemination of a primary tumors to distant organs [ 9 ]., intra-tumor heterogeneity has been proven through single-cell sequencing of lung cancer [ 10 ]. Tumor heterogeneity creates a challenge for treatment planning as well as prediction of response to treatment.…”
Section: Introductionmentioning
confidence: 99%